Texting the underworld - Booraem, Ellen (Dial Books for Young Readers, 2013)
Conor O'Neill faces his cowardice and visits the underworld to bargain with the Lady who can prevent the imminent death of a family member, but first Ashling, the banshee who brought the news, wants to visit his middle school.